Modern methods of counteracting urban heat islands - Michał Musiał; Anna Pomykała; Lech Lichołai (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
This article presents a complete compendium of knowledge in the field of urban heat island mitigation. The article presents both conventional methods and artificial intelligence algorithms to counteract urban heat islands. The study presents a systematisation of the causes and effects of urban heat islands in the context of climate change, urbanisation and the impact of human activity. Strategies for mitigating the effects of urban heat islands in the short term and in the long term have also been presented. Moreover, the article presents the advantages, disadvantages and limitations of artificial intelligence algorithms and techniques. The types and limitations of each group of algorithms are presented in the context of their application for urban data and resources management. A new aspect of the article is a holistic perspective of the problem of counteracting urban heat islands, taking into account the genesis of their generation and the limitations of conventional and artificial intelligence methods.